ANALISIS PENETAPAN HARGA SEWA RUMAH SUSUN SEDERHANA SEWA ( Studi Kasus Rumah Susun Sederhana Sewa Desa Panggungharjo Kecamatan Sewon Kabupaten Bantul ) - , Agung Murhandjanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the modest apartment rental lease panggungharjo Sewon Bantul based on operating and maintenance costs as well as the cash value of rural land investment Panggungharjo, analyze a simple apartment rental lease with the cost approach method, analyzing rents simple flats rent based on ability and desire pay (ATP and WTP) of the target group of residents rent a modest apartment and set a rental price above is based on several variables. method of analysis used in this study is the market data comparison approach, cost approach, the estimated rental value and descriptive statistics. Data used in this study is the primary data and data obtained from the primary sekunder.data survey results and interviews with managers of rental panggungharjo simple flats and the occupants or tenants secondary susun.data obtained from the department of public works as the manager of Bantul simple flats Panggungharjo lease. Cost benefit analysis of the beneficiaries land Value of assets and investments in the construction of simple flats rent Panggungharjo very large and expensive it becomes an obligation for managers, governments, along with the stake holders together to maintain and care for simple flats lease asset, if the rents were not determined to cover operating costs and maintenance of the government should provide rent subsidies to the end that the value of assets and investments simple flats rent Panggungharjo maintained